A study of contemporary Ghana : the economy of Ghana - Birmingham, Walter Barr.; Neustadt, I.; Omaboe, E. N. (London : George Allen & Unwin Ltd, 1966)
The survey is presented in an orthodox economic framework. After an introductory chapter by Mr. Omaboe, there is a detailed account in macroeconomic terms of the structure of the economy, its performance over the period of 1955-62, its sectoral structure in 1960, regional aspects and patterns of consumption. There then follows an analysis of the factors of production, leading on to a survey of the different sectors of the economy- agriculture, mining, manufacturing industry, monetary system and external trade. The final section of the book deals with policy and planning. This consists of two case studies-cocoa, and the Volta River project-and two chapters on economic control and the process of planning.
Volume One.
Includes index.
Includes bibliographical references: p. 464-468.
aia 02/11/2017
Loans
Keywords: Ghana- Economic conditions; Ghana- Social Conditions; Ghana